2009
DOI: 10.1111/j.1742-4658.2009.07361.x
|View full text |Cite
|
Sign up to set email alerts
|

The pro‐form of BMP‐2 interferes with BMP‐2 signalling by competing with BMP‐2 for IA receptor binding

Abstract: Pro‐forms of growth factors have received increasing attention since it was shown that they can affect both the maturation and functions of mature growth factors. Here, we assessed the biological function of the pro‐form of bone morphogenetic protein‐2 (BMP‐2), a member of the transforming growth factor β (TGFβ)/ΒΜP superfamily. The role of the 263 amino acids of the pro‐peptide is currently unclear. In order to obtain an insight into the function of the pro‐form (proBMP‐2), the ability of proBMP‐2 to induce a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
29
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…The type II receptors ActRIIA, ActRIIB, and BMPRII compete with the pro-domain for binding to the growth factor resulting in a stepwise prodomain displacement (26). The partially latent BMP2⅐pro-domain complex was shown to bind to type I receptor BMPRIA but not to type II receptor BMPRII (27). The pro-domain is FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…The type II receptors ActRIIA, ActRIIB, and BMPRII compete with the pro-domain for binding to the growth factor resulting in a stepwise prodomain displacement (26). The partially latent BMP2⅐pro-domain complex was shown to bind to type I receptor BMPRIA but not to type II receptor BMPRII (27). The pro-domain is FIGURE 7.…”
Section: Discussionmentioning
confidence: 99%
“…For a long time it was assumed that processing of pro-BMPs would take place in the Golgi and that only the processed forms without the pro-domains would be secreted. Association of the pro-domain with the mature growth factor can bind to the extracellular domain of BMPRIA (46). Furthermore, it is known from the literature that, pro-BMP-2 shows no binding characteristics to the extracellular domain of BMPRII (46).…”
Section: Discussionmentioning
confidence: 99%
“…Association of the pro-domain with the mature growth factor can bind to the extracellular domain of BMPRIA (46). Furthermore, it is known from the literature that, pro-BMP-2 shows no binding characteristics to the extracellular domain of BMPRII (46). It is still an open question whether all of the BMP-2 is secreted in its cleaved mature form or if some is secreted as a pro-form.…”
Section: Discussionmentioning
confidence: 99%
“…Studies with the purified pro-form of BMP2 showed that the presence of the proregion inhibits binding to BMP receptor II, while not affecting binding to BMP receptor type I (Hauburger et al, 2009). Limited proteolysis of the proregions and/or pro-forms of BMP2, GDF5 and the Drosophila orthologue of BMP2, decapentaplegic (dpp), led to the identification of protease-resistant sub domains within the proregions (Kuhfahl et al, 2011).…”
Section: The Functionally Versatile Bmp Proregionsmentioning
confidence: 99%